Seeding Date and Bur Treatment Affect Establishment Success of Dormant‐Seeded Buffalograss. (1st July 2017) - Li, Luqi; Sousek, Matthew D.; Amundsen, Keenan L.; Reicher, Zachary J.
Abstract : Core Ideas: Dormant seeding of buffalograss in November can be as effective as traditional May seeding. Commercially potassium nitrate treated burs resulted in consistently higher cumulative germination regardless of seeding date. Commercial treatment of burs may not be necessary when dormant seeding in November, but maximized buffalograss germination following an exceptionally dry winter. Dormant seeding is common for establishing cool‐season turfgrasses, but minimal information exists on dormant seeding of the native warm‐season buffalograss [ Buchloë dactyloides (Nutt.) Engelm.] in the Midwest and northern Great Plains of the United States. The objective of these studies was to determine the effect of commercial KNO3 seed treatment on cultivar Cody buffalograss germination when seeded at various dates in winter and spring. Cody buffalograss burs were either commercially treated or untreated and both were seeded in the field the third week of November, January, March, or May. Buffalograss cover was rated monthly until the following August. Dormant seeding in November, January, or March was as effective as seeding at the traditional May timing. Commercial treatment of burs may not be necessary when dormant seeding in November, but treated bur maximized buffalograss germination following an exceptionally dry winter. In a second study, buffalograss burs from the same source as the initial study were buried in mesh packets in the field in the third week of each month from November through April. All packets were transferred to a greenhouse in May to test germination. Commercially treated burs resulted in consistently higher cumulative germination regardless of seeding date. Cumulative germination data agreed with initial field study in that dormant seeding of buffalograss in November can be as effective as traditional May seeding.